The Prevalence of Dental Anxiety and its Relation to Oral Health Related Quality of Life among Geriatric Population with Dental Treatment Needs at a Dental College in Vadodara City: A Cross-sectional Study - Chauhan, Sameer; Mahajan, Neerja; Sethuraman, Rajesh (International Journal of Psychosocial Rehabilitation, 2020)
Background and Objectives: Anxiety about dental treatments and fear of pain associated with dental pathologies as well as dental procedures remain widespread. The era of modern science has witnessed tremendous advancements in the field of pain control and patient management. Despite these advances, anxiety related to dental treatment and the fear of pain associated with it remain among the general population. Literature suggested that dental anxiety is also prevalent even in older age. However, very limited data are available in the literature about the relationship of dental anxiety (DA) and oral health-related quality of life(OHRQoL) among the geriatric population. The aim of this observational, cross-sectional study was to analyze the relationship between DA and OHRQoL in a geriatric population with dental treatment needs.Materials and Methods: 172 participants above 60 years of age who reported to K. M. Shah Dental College and Hospital with dental treatment needs were enrolled into the study. The measurements of DA were collected by the Modified Dental Anxiety Scale (MDAS), and oral health-related quality of life (OHRQoL) was assessed with the Geriatric Oral Health Assessment Index (GOHAI).Results: A total of 170 participants were included in the statistical analysis (two were excluded due to missing key answers). No gender dependency was observed. A comparison of answers regarding DA and OHRQoL revealed a significant interdependence (p = 0.0109); highly anxious patients were 3.77 times more likely to suffer from poor quality of life compared with less anxious ones.Conclusion: This cross-sectional study of geriatric patients seeking dental treatment at a dental college in Vadodara city found that increased dental anxiety was associated with an impaired oral health-related quality of life.